2021
DOI: 10.1530/eje-21-0007
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-7977 in CD4+ T cells is associated with multiplex autoimmunity in patients with Addison’s disease

Abstract: Objective: Autoimmune Addison’s disease (AD) results from a combination of the genetic predisposition, unclear environmental triggers and ensuing immune dysfunction. MicroRNA molecules (miRNAs) are involved in post-transcriptional regulation of numerous target genes, hence may affect the immune function and promote autoimmunity. A deregulated miRNAs profile was reported in several autoimmune conditions. Our study was aimed at a global analysis of miRNA expression in CD4+ T cells from patients with AD. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…We speculate that PCED1B-AS1 may competitively combine with has-miR-7977 to change the expression of downstream sepsis-related mRNAs. Fichna et al ( Fichna et al, 2021 ) suggested that miR-7977 is increased in CD4+T cells of autoimmune Eddie’s disease patients and plays a crucial function in autoimmune diseases; Horiguchi et al ( Horiguchi et al, 2016 ) found that miR-7977 can reduce the hematopoietic support ability of bone marrow CD34 + cells. Our results show that LINC01422 can combine not only with has-miR-7977, but also competitively with has-miR-197-3p.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that PCED1B-AS1 may competitively combine with has-miR-7977 to change the expression of downstream sepsis-related mRNAs. Fichna et al ( Fichna et al, 2021 ) suggested that miR-7977 is increased in CD4+T cells of autoimmune Eddie’s disease patients and plays a crucial function in autoimmune diseases; Horiguchi et al ( Horiguchi et al, 2016 ) found that miR-7977 can reduce the hematopoietic support ability of bone marrow CD34 + cells. Our results show that LINC01422 can combine not only with has-miR-7977, but also competitively with has-miR-197-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have proven the involvement of miRNAs in this condition. A significant upregulation of miR-7977 was found in CD4 + T cells obtained from the peripheral blood of patients with autoimmune Addison’s disease compared to healthy controls ( Fichna et al, 2021 ). Additionally, a positive correlation was found between the amount of co-occurring autoimmune disorders and the abundance of miR-7977, as well as with the expression of miR-7977 and circulating autoantibodies against thyroid peroxidase (aTPO).…”
Section: Introductionmentioning
confidence: 99%
“…Although the particular target of miR-7977 is still unknown, 18 potential targets involved in autoimmunity were identified, and they are ARRB1, CD80, CEBPG, CMKLR1, CRP, ENTPD1, HIPK2, HRH4, IL16, JAG1, MAVS, P2RY2, SEMA3G, SEMA4C, SIRPA, SLC11A, THRB, and VGLL3. These genes are thought to be involved in immune response, primary cellular component regulation, and metabolic processes ( Fichna et al, 2021 ). Similarly, miRNA-455 and miRNA-125a were significantly downregulated in the adrenal gland of Allgrove syndrome patients with adrenal insufficiency ( Bitetto et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%